Characterization of the complete chloroplast genome of Rosa laevigata var. leiocarpus in China and phylogenetic relationships. Issue 2 (2nd April 2020) - Sun, Zhiqian; Shi, Shi; Pang, Xingchen; Chen, Jingfeng; Wu, Yongbin
Abstract: Rosa laevigata var. leiocarpus has excellent edible, ornamental and medicinal value in China. In this study, we presented the complete chloroplast genome of R. laevigata var. leiocarpus . The whole chloroplast genome is 156, 373 bp in size, consisting of a pair of inverted repeats (IR 26, 047 bp), a large single-copy region (LSC 85, 494 bp) and a small single-copy region (SSC 18, 785 bp). The R. laevigata var. leiocarpus chloroplast genome encodes 139 annotated known unique genes including 92 protein-coding genes, 39 tRNA genes, and 8 rRNA genes. Phylogenetic analysis based on chloroplast genomes of 18 plant species reveals that R. laevigata var. leiocarpus was clustered and closest with Rosa roxburghii and also closer to other Rosa species in the evolutionary relationship.